Clinical nutrition and human rights. An international position paper. Issue 6 (June 2021) - Cardenas, Diana; Correia, Maria Isabel Toulson Davisson; Ochoa, Juan B.; Hardy, Gil; Rodriguez-Ventimilla, Dolores; Bermúdez, Charles E.; Papapietro, Karin; Hankard, Régis; Briend, André; Ungpinitpong, Winai; Zakka, Katerina Mary; Pounds, Teresa; et al.
Summary: The International Working Group for Patients' Right to Nutritional Care presents its position paper regarding nutritional care as a human right intrinsically linked to the right to food and the right to health. All people should have access to food and evidence-based medical nutrition therapy including artificial nutrition and hydration. In this regard, the hospitalized malnourished ill should mandatorily have access to screening, diagnosis, nutritional assessment, with optimal and timely nutritional therapy in order to overcome malnutrition associated morbidity and mortality, while reducing the rates of disease-related malnutrition. This right does not imply there is an obligation to feed all patients at any stage of life and at any cost. On the contrary, this right implies, from an ethical point of view, that the best decision for the patient must be taken and this may include, under certain circumstances, the decision not to feed. Application of the human rights-based approach to the field of clinical nutrition will contribute to the construction of a moral, political and legal focus to the concept of nutritional care. Moreover, it will be the cornerstone to the rationale of political and legal instruments in the field of clinical nutrition.